Further studies utilizing hormones to alter estrous cycles and fertility - Stevenson, Jeffrey S.; Stewart, R.E.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
In one large dairy herd, we examined the reproductive performance of 943 cows following early postpartum hormonal therapy utilizing gonadotropin-releasing hormone (GnRH or Cystorelin®) and prostaglandin F2-alpha (PGF). None of our hormonal treatments improved reproductive efficiency in this herd, whereas earlier studies at the KSU Dairy Teaching and Research Center had proved beneficial. However, cows given PGF to induce estrus at the beginning of the breeding period had similar reproductive performance to control cows, suggesting a potential use for one injection of PGF to allow the breeding of more cows by a target date after calving (e.g., by 65 days).
Keywords: Dairy; Hormones; Estrous cycle; Fertility; Gonadotropin-releasing hormone (GnRH); Prostaglandin F2-alpha